Poverty And Environmental Impacts of Electricity Price Reforms In Montenegro - Silva, Patricia, 1973- 1973- (The World Bank, 2007)
The Government of Montenegro is preparing an electricity tariff reform due to recent developments in the national and regional electricity markets. Electricity tariffs for residential consumers in Montenegro are likely to gradually increase by anywhere from 40 to over 100 percent. This significant price rise will impose a heavy burden on poor households and it may adversely affect the environment. In an ex-ante investigation of the welfare impact of this price increase on households in Montenegro, the authors show that the anticipated price increase will result in a significant increase in households' energy expenditures. A simulation of alternative policy measures analyzes the impact of different tariff levels and structures on the poor and vulnerable households in particular. Higher electricity prices could also significantly increase the proportion of households using fuelwood for space heating